2008
DOI: 10.1111/j.1471-0528.2007.01655.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of interleukin‐1RN and interleukin‐1β genes and risk of cervical cancer

Abstract: Objectives Inflammation plays a major role in pathogenesis of cervical cancer. We planned to study whether polymorphisms in inflammation-related genes, IL-1RN (VNTR) and IL-1b (-511C/T), are associated with risk of cervical cancer.Design Case-control study.Setting Uttar Pradesh state in India.Sample One hundred and fifty, histopathologically confirmed cases with cervical cancer and 162 age-, ethnicity-matched, cervical cytology negative, healthy controls were recruited to this study.Methods Genotyping of IL-1R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…Therefore, genetic variation of immune system factors may influence susceptibility to cervical cancer (Zur Hausen, 2000;Konac et al, 2007;Jumnainsong, et al, 2007;Schlee et al, 2007;Han et al, 2008;Yu et al, 2009). Recent research has investigated SNPs in CD83, IL-1, IL-6, IL-12, VEGF, and nuclear factor-kappa B in cervical cancer patients (Konac et al, 2007;Zhang et al, 2007;Singh et al, 2008;Castro et al, 2009;Chen et al, 2009;Zhou et al, 2010); however, it remains to be elucidated how the genetic variation is involved in the regulation of the immune response and tumorigenesis (Zhang et al, 2007;Yu et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, genetic variation of immune system factors may influence susceptibility to cervical cancer (Zur Hausen, 2000;Konac et al, 2007;Jumnainsong, et al, 2007;Schlee et al, 2007;Han et al, 2008;Yu et al, 2009). Recent research has investigated SNPs in CD83, IL-1, IL-6, IL-12, VEGF, and nuclear factor-kappa B in cervical cancer patients (Konac et al, 2007;Zhang et al, 2007;Singh et al, 2008;Castro et al, 2009;Chen et al, 2009;Zhou et al, 2010); however, it remains to be elucidated how the genetic variation is involved in the regulation of the immune response and tumorigenesis (Zhang et al, 2007;Yu et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Yu et al (2009) replicated this study and confirmed the possible role of CD83 polymorphisms in cervical carcinogenesis. Further, polymorphisms in interleukin (IL)-1, IL-6, IL-12, vascular endothelial growth factor (VEGF), and nuclear factor-kappa B have been associated with the risk of cervical carcinoma (Konac et al, 2007;Singh et al, 2008;Castro et al, 2009;Chen et al, 2009;Zhou et al, 2010). Collectively, these findings strongly suggest that polymorphisms in genes may influence susceptibility to cervical cancer.…”
Section: Introductionmentioning
confidence: 92%
“…However, previous studies considering the relations between the CTLA-4 and IL-1 polymorphisms and cervical cancer have produced inconsistent results [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. These inconsistencies may be due to the sample sizes, racial/ethnic differences in allele frequencies, or publication bias [26].…”
mentioning
confidence: 69%
“…Two were excluded because one was about a different disease [32] and one was about a different polymorphism [33]; thus, 15 studies in total met our inclusion criteria. These consisted of 8 studies on the CTLA-4 polymorphism [12][13][14][15][16][17][18] and 7 on the IL-1 polymorphism [19][20][21][22][23][24][25] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…IL-1 is a critically important inflammatory cytokine that is the proposed 'gatekeeper' of inflammation, having numerous and diverse roles in regulating injury and infection 471 . Genetic variation at the rs16944 (G/A) locus has been implicated in several diseases that have an inflammatory component including, but not limited to, gastric cancer 472 , type II diabetes mellitus 473 , osteoarthritis 474 , cervical cancer 475 , and gastroesphageal reflux disease 476 . Genetic association studies have also provided evidence on the involvement of rs16944 in schizophrenia, with reports that implicate the A-allele in illness endophenotypes like elevated brain activation and brain volume reductions 276,277 , and the G-allele in overall disease risk 477,478 .…”
Section: Il-1 Variants and Bdnf Val66met Are Associated With Aiwgmentioning
confidence: 99%